Peran Moderasi Brand Awareness dalam Pengaruh Perceived Usefulness, Expert Involvement, dan Playfulness Konten Video Pendek terhadap Lead Generation di Perusahaan B2B - Rajabuan, Ance Costansa; Marufi, Muqorrobien; Miswanto, Miswanto; Biyanto, Frasto; Siregar, Baldric (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study examines the influence of Perceived Usefulness, Expert Involvement, and Playfulness in B2B short video marketing content on Lead Generation, moderated by Brand Awareness. Data from 200 B2B professional respondents were analyzed using PLS-SEM with SmartPLS. Results indicate that all three content characteristics positively and significantly impact Lead Generation. Brand Awareness positively moderates the relationship between Expert Involvement and Lead Generation. Uniquely, Brand Awareness negatively moderates the relationship between Playfulness and Lead Generation, suggesting that for well-known B2B brands, excessive playfulness can be counterproductive. Managerial implications advise prioritizing usefulness and expert involvement, and adapting playfulness based on Brand Awareness levels.